Representasi kekerasan seksual terhadap perempuan dalam Film “2037” (studi analisis semiotika Ferdinand de Saussure) - Ika Amiliya Nurhidayah; Syamsul Bakhri; M. Achwan Baharuddin (Universitas Negeri Malang, 2023)
One of the developments in communication technology that occurs today is the presence of various communication channels or 'media' in the process of delivering ideas, messages, or ideas. The variety of communication media has become the most effective method today in the formation of a person's point of view and behavior. In this study, researchers are interested in making one of the three types of communication media, namely audio-visual communication media in the form of films. Film is claimed to be a mass media that has a dominant influence than other media, this is due to the influence of psychology on films which is fundamental in the formation of opinions and people's psyche. Researchers are interested in examining a film entitled